Antimalarial Activity of Meriandra dianthera Leaf Extracts in Plasmodium berghei-Infected Mice. (12th February 2020) - Hagazy, Kalay; Sibhat, Gereziher G.; Karim, Aman; Tekulu, Gebretsadkan H.; Periasamy, Gomathi; Hiben, Mebrahtom G.
Abstract : Objective . To evaluate the antimalarial effect of aqueous methanolic extract and solvent fractions of Meriandra dianthera leaves against Plasmodium berghei in mice model. Method . M. dianthera leaves were extracted with 80% methanol and dried. The dried crude extract was then defatted and further fractionated with chloroform, ethyl acetate, and butanol. Acute oral toxicity test was performed as per the Organization for Economic Cooperation and Development guideline 425. Peter's 4-day suppressive test was used to determine the in vivo antimalarial activity of the extract and fractions. Result . The crude leaf extract of Meriandra dianthera showed parasite inhibition of 42.28% and 45.52% at doses of 400 and 600 mg/kg, respectively, as compared to the negative control. Moreover, the mice which received chloroform and aqueous fractions at the dose of 400 mg/kg/day showed significant (P < 0.001 ) chemosuppression compared to the negative control. Both the extract and fractions were able to prevent P. berghei induced body weight loss and body temperature reduction and also increased the survival time of the mice as compared to the negative control. The aqueous methanolic leaf extract of M. dianthera showed no gross signs of toxicity or mortality in mice until a single oral dose of 2000 mg/kg. Conclusion . The extracts of M. dianthera leaves showed promising antimalarial activity, with no sign of toxicity and therefore may support its traditional use for the treatment of malaria.